IMPLEMENTASI NILAI-NILAI KEWIRAUSAHAAN SYARIAH PADA MATA KULIAH EDUPREUNER PROGRAM STUDI PGMI STAI SUNAN PANDANARAN YOGYAKARTA - Sa'adah, Barirotus; Mushawir, Mushawir (MIDA : Jurnal Pendidikan Dasar Islam, 2024)
Research entitled Implementation of Sharia Entrepreneurship Values in Edupreuner Courses, PGMI STAI Sunan Pandanaran Yogyakarta Study Program. This research aims to find out how Sharia Entrepreneurship values are implemented in the Edupreuner course at the PGMI STAI Sunan Pandanaran Study Program. Data analysis in this research is descriptive analysis by reducing data from respondents' answers. Reducing data means summarizing, selecting the main things, focusing on the important things, looking for themes and patterns. In this way, the reduced data will provide a clearer picture, and make it easier for researchers to collect further data, and look for additional data if needed. (Sugiyono, 2009) The results of the research are that in direct practice, students are able to implement sharia entrepreneurship values well , the sharia entrepreneurial values that they apply include: honesty, no elements of lying, no elements of usury, maintaining product halal, and upholding sales and purchase agreements or agreements between both parties.